Politics against social exclusion and their relation with Social Pedagogy: Guaranteed Minimum Income programs and Basic Income. - Rodríguez, Juan Ramón (Education Policy Analysis Archives, 2013)
This paper discusses the role of social pedagogy in the context of struggles for economic and political democracy, particularly regarding Guaranteed Minimum Income (GMI) programs, which are some of the most significant policy initiatives to combat social exclusion in modern Welfare States. The author argues that a more effective alternative to these programs, which are rooted in liberal thought, is a Basic Income (BI) model. Not to be confused with a charity instrument against poverty, BI is a tool in a broader anti-capitalist strategy. Whether it operates in the context of GMI or BI, social pedagogy will have different expressions, goals, approaches and practices. In the context of BI and its ideological roots in Anarchist and solidarity Marxism, social pedagogy can critically address issues such as social inequalities, banking education, the relationship between education and work, and direct democracy.